Performance of a Moringa Leaf Dehumidification Drying System Using Peltier Effect Thermoelectric Cooling - Mhd Iqbal Nusa; Budi Suarti; Muhammad Said Siregar (The University of Lampung, 2025)
The study focuses on a drying system that integrates a rack-type convective dryer with a Peltier effect thermoelectric cooler to optimize the drying process of moringa leaves. This system is designed to achieve lower drying temperatures, which is essential for preserving the quality of the leaves. To evaluate the performance of this dryer, researchers use temperature and relative humidity data to construct a programmed psychrometric diagram. This diagram helps in calculating crucial parameters such as the absolute humidity and the specific volume of the drying air. These calculations are essential in determining the drying rate of moringa leaves. The results indicated that moringa leaves dried on drying rack-1 exhibited a higher drying rate compared to those on drying rack-2. Additionally, a drying air speed of 2.1 m/sec yielded a superior drying rate compared to a lower air speed of 1.5 m/sec. After 5.0 hours of drying, the Moringa leaves achieved a moisture content of 8.6% (wb) with a drying air speed of 2.1 m/sec, 9.3% (wb) with a speed of 2.6 m/sec, and 13.9% (wb) with a drying air speed of 1.5 m/sec. The drying process maintains a maximum temperature 59.3°C, placing it within the low-temperature drying category, which helps preserve the physicochemical quality of the dried Moringa leaves. Keywords: Dehumidification drying, Peltier effect thermoelectric cooling, Moringa leaves, Programmed Psychrometric Calculations.